Designing Inclusive Islamic Education: A Democracy and Multiculturalism-Based Approach - Jobeda Khanom; Md Tarequl Islam (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to analyze the design and implementation of inclusive Islamic education in democratic and multicultural contexts, especially in integrating Islamic values with learning practices that respect diversity. Theoretical framework: The theoretical framework of this research combines the values of Islamic education, democratic principles, and multicultural education approaches as the basis for building inclusive learning. Literature review: The literature review highlights the importance of Islamic education that is inclusive and responsive to diversity, but it is still dominated by conceptual studies, so an empirical approach is needed. Methods: The research uses qualitative methods with interviews, observation, and document analysis techniques in several Islamic educational institutions. Results: Results show that inclusive Islamic education is implemented through flexible curriculum, participatory learning, appreciation of diversity, and leadership based on Islamic values, although there are still constraints on teacher readiness and resources. Implications: There is a need for a more systematic integration between Islamic values, democracy, and multiculturalism, as well as teacher capacity building and policy support. Novelty: This research offers an empirical model of inclusive Islamic education that integrates Islamic values with democratic and multicultural approaches in a practical way.